Internationalization of Higher Education and the Advantage of Diaspora - Rizvi, Fazal (International Higher Education, 2023)
With their policies of internationalization, higher education institutions have increasingly begun to develop diaspora strategies to take advantage of the cultural diversity and transnational connectivity of their international students and faculty. This article shows how the idea of diaspora is now understood and deployed by higher education institutions to foster competitive advantage.